Credit Risk, Lending Activity, and Bank Performance Under Inflationary Pressure: Evidence From Islamic Banking in Indonesia - Mahmudatus Sadiyah; Eva Harmelia Valentina (Journal of Halal Review, 2026)
Objective: This study aims to analyze the effect of financing risk and financing distribution activities on the performance of the Islamic banking industry in Indonesia, as well as to examine the role of inflation as a macroeconomic factor that influences this relationship. The main focus of this study is on the dynamics of the profitability of the Islamic banking industry in the face of financing expansion and inflationary pressures. Research Design & Methods: This study uses a quantitative approach with an explanatory design based on quarterly time series data. The unit of analysis is at the level of the Islamic banking industry in Indonesia. The dependent variable is industry performance, proxied by return on assets (ROA), while the independent variables include financing risk (non-performing financing/NPF), total financing transformed into natural logarithms, and inflation. The estimation is performed using the Common Effect Model (CEM) regression model, with additional testing through an interaction model to capture the role of inflation as a conditional factor. Findings: The results indicate that financing expansion has a negative and significant effect on ROA, suggesting that growth in financing has not been fully translated into improved profitability. Inflation exhibits a positive and statistically significant effect on ROA within the observed sample period, indicating the industry's capacity to adjust margins under prevailing inflationary conditions. Financing risk shows a negative but statistically insignificant effect. Furthermore, the interaction term between NPF and inflation is negative, implying that higher inflation intensifies the adverse effect of financing risk on industry performance. Implications & Recommendations: These findings emphasize the importance of strengthening financing quality, risk management, and macroeconomic policy coordination to maintain the sustainability of the Islamic banking industry's performance. Contribution & Value Added: This study provides empirical contributions by presenting industry-based evidence on the relationship between financing risk, financing, and inflation on the profitability of Islamic banking in developing countries.